(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
The article presents the results of a study on clinical, laboratory, and immunoinflammatory characteristics in patients with arterial hypertension (AH) and in those with combined pathology of AH and ischemic heart disease (IHD). A total of 78 patients were examined and divided into two groups: patients with isolated AH (Group I) and patients with AH complicated by IHD (Group II). The control group consisted of conditionally healthy individuals.